First generic records of tardigrades (Tardigrada) for the province of Victor Fajardo, Peru - Macedo Bedoya, Jehoshua (2025)
Despite their widespread global distribution, studies on tardigrades in Peru are limited. This paper reports for the first time the presence of the genera Echiniscus, Macrobiotus, Milnesium, Ramazzottius, and Viridiscus in the locality of Llusita, located in the province of Víctor Fajardo, Ayacucho. The specimens were collected from epiphytic mosses and analyzed using the sieving method for tardigrade extraction. A total of 65 individuals were identified, with the genera Ramazzottius and Viridiscus being the most notable, which are reported for the first time in the country.